The Safety of Land Transport: Challenges and Perspective - Malave Drouet, Sara (2018)
Overview. Ground transportation is that transfer that takes place on the surface of the Earth, the vast majority are on wheels, it has its origin in the transfer of the human being, who, by the need to move or transfer their loads, according to weight or distance He saw the need to improve this mechanism, from the rivers to the Mainland. The passage of time caused the appearance of the wheel in the future of engine, who was also immersed in its evolution and improvement, first use the fire, water, steam and then see the internal combustion engine, enhanced with the discovery of oil. Today the transportation points to new alternatives such as electricity, solar and artificial intelligence.